In the Footsteps of Didymus: On the Subject of two Didymic Scolii to Euripides’ Medea and the Interpolation of a Memorable Verse - Colli, Giulia (Lexis (Venezia, Online), 2024)
This paper aims at reconstructing Didymus’s opinion about the repetition of line 356a = 380 of Euripides’ Medea , and at the same time to discuss the authenticity of this repetition in the first episode (356a = 380) as well as in the prologue (l. 41). On one hand, it will be argued that Didymus considered l. 380 authentic whereas l. 356a interpolated by ancient actors and that l. 356a was at his time yet discontinuously attested; on the other hand, that ll. 41 and 356a were both interpolated in antiquity, possibly by different hands, due to the memorability and pathetic effectiveness of the line.